Răspuns :
Răspuns:
Explicație pas cu pas:
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);
2. Fie a şi b numere reale nenule astfel în
a) a=b(2+√3);